The American Friend: Culture and Imperialism in times of “Good Neighbor Policy” - Santana, Sandro (2020)
This article proposes a reflection on the role of the Hollywood industry as an instrument of coloniality in Latin America, during the Politics of “Boa Vizinhança”, based on the performance of Carmen Miranda in Hollywood films. Therefore, I use as theoretical contribution the concepts of coloniality of power, of knowing and of being, and of geopolitics of knowledge, present no thought of Quijano (2005, 2009), Mignolo (2003) and Maldonado-Torres (2009), bem as a contribution of post-colonial intellectuals, such as Bhabha (2005) and Said (1995). At the beginning, on board or in the historical context that helped to “promote” or the succession of Carmen to the United States and to the stereotyped condition that the singer and actress became known during her stay in America. To follow, I dialogue with the positions of two thinkers cited and as considerations on the role of the Hollywood industry as an instrument of affirmation of "colonial difference". At the end of the year, I focus on the needs of Public Policies for the confrontation of the coloniality of the modern / colonial image, taking into account not only the economic field, but, mainly, the city of symbolic dimensions.